The AHA’D (One narrator) Hadith in compliance with legal laws and point of view of Fundamentalists in what drops in case of suspicious some of Fiqh (Jurisprudence) branches based - Al-Zaidani, Dhaifullah Hadi Ali (Journal of Islamic Sciences, 2020)
The research treats the issue of AHA’D (One narrator) Hadith, its compliance with legal laws and point of view of Fundamentalists in what drops in case of suspicious. The research lights on the different points of view of Scholars about AHA’D Hadith, they consider it in the legal laws, whereas most Hadiths are AHA’Ds. The research mentioned at the end some of Fiqh (Jurisprudence) branches based on this issue and finally the results of the research.